Peningkatan Pembelajaran Menggosok Gigi Melalui Media Video Tutorial Pada Anak Disabilitas Intelektual Sedang Di SLB Negeri Aek Kanopan - Ely Yusnita Pane; Mega Iswari; Rahmahtrisilvia Rahmahtrisilvia; Syari Yuliana (Lembaga Riset dan Inovasi Almatani, 2026)
This study aimed to improve toothbrushing skills through the use of video tutorial media among students with moderate intellectual disabilities in Grade II at SLB Negeri Aek Kanopan. The research employed a Classroom Action Research (CAR) design conducted at SLB Negeri Aek Kanopan. The research subjects consisted of two students with moderate intellectual disabilities, identified as CA and RN. Based on the initial assessment, the toothbrushing skills of both subjects were categorized as low, with achievement percentages of 37.5% for CA and 45% for RN. The study was carried out in two cycles, each comprising the stages of planning, implementation, observation, and reflection. The results of observations in Cycle I indicated an improvement in toothbrushing skills, with both CA and RN achieving 47.5%. Furthermore, a very significant improvement was observed in Cycle II, in which both subjects reached an achievement percentage of 100%. Data were collected through observation using a toothbrushing skills assessment checklist, while data analysis was conducted using descriptive quantitative methods by comparing achievement results across cycles. The findings demonstrate that the use of video tutorial media is effective in improving toothbrushing skills among students with moderate intellectual disabilities. These results indicate that visual- and audio-based instructional media can assist students in understanding self-care activity procedures more concretely and engagingly, in accordance with the learning characteristics of students with moderate intellectual disabilities.